APPLICATION FOR SECURITY ENCRYPTION TECHNIQUES DATA ON E-MAIL - Darwito Darwito; Sahni Damerianta P. Skom. MM (Jurnal Sistem Informasi, 2000)
The need for information is increasing, along with the development of computertechnology which require data as input and produces an output in the form ofinformation, which can be used for certain purposes. With the increasingdevelopment of computer technology, we are more easily obtain the desiredinformation and faster. Confidential information requiring special handling, both ingetting that information from the source of information, during the journey to theplace recipient information, or when information is received. Thus, if there is aconfidential news and apparently there are certain parties who deliberately orinadvertently read the electronic mail we receive, we will suffer losses. To overcomethis a most unusual way is to protect such data through password protection at thetime of access. But if just using a password that data can still be accessed through theaccess way is not through the standard application. Therefore one of the best ways isto encode or scramble the information contained in these data based on a pattern or acertain key, which can only be read back to the real meaning by the parties entitled.